The Psycholocial challenges facing Unaccomopanied Refugee Children in Urban Zimbabwe - Chemdza, Nely Cristina (My University, 2006)
THE PSYCHOSOCIAL CHALLENGES OF UNACCOMPANIED REFUGEE CHILDREN IN URBAN ZIMBABWE Abstract This study explores the psychosocial coping mechanisms of unaccompanied migrant children in Harare, Zimbabwe. While refugees who stay in camps are provided formal assistance through various forms of psychosocial intervention, those who live in cities must typically rely on their own resources and strategies. Using existing academic literature on psychosocial interventions and coping strategies in camps as a comparative referent, this study documents and explains the responses on unaccompanied displaced youth in Harare. Given that this research focuses on the exploration of the informal coping strategies of unaccompanied refugee children a qualitative research is the most preferable method on collecting data. The instruments for collecting the data were semi-structured interviews with key informants and unaccompanied refugee children. Although this project is for academic purposes it is expected that the findings can also be used to for advocacy and programme formulation to meet the psychological needs of unaccompanied refugee children in Zimbabwe as the country undergoes this transitional phase.
Student Number:0400612E Faculty:Humanities Degree:MA
Keywords: Coping Machanism of Unaccompanied migrant children in Harare,Zimbabwe; This Intrument Qualitative Research is the most preferable method on collecting Data for That Informal Coping Mechanism